Building an adaptive brain across development: targets for neurorehabilitation must begin in infancy - Edgin, Jamie O.; Clark, Caron A.; Massand, Esha; Karmiloff-Smith, Annette D. (Frontiers in Behavioral Neuroscience, 2015)
Much progress has been made toward behavioural and pharmacological intervention in intellectual disability, which was once thought too difficult to treat. Down syndrome research has shown rapid advances, and clinical trials are currently underway, with more on the horizon. Here, we review the literature on the emergent profile of cognitive development in Down syndrome, emphasizing that treatment approaches must consider how some “end state” impairments, such as language deficits, may develop from early alterations in neural systems beginning in infancy. Specifically, we highlight evidence suggesting that there are pre- and early postnatal alterations in brain structure and function in Down syndrome, resulting in disturbed network function across development. We stress that these early alterations are likely amplified by Alzheimer’s disease progression and poor sleep. Focusing on three network hubs (prefrontal cortex, hippocampus, and cerebellum), we discuss how these regions may relate to evolving deficits in cognitive function in individuals with Down syndrome, and to their language profile in particular.